2010
DOI: 10.1007/s00421-010-1411-0
|View full text |Cite
|
Sign up to set email alerts
|

Active regulation of cerebral venous tone: simultaneous arterial and venous transcranial Doppler sonography during a Valsalva manoeuvre

Abstract: The aim of this study was to analyse the cerebral venous outflow in relation to the arterial inflow during a Valsalva manoeuvre (VM). In 19 healthy volunteers (mean age 24.1 +/- 2.6 years), the middle cerebral artery (MCA) and the straight sinus (SRS) were insonated by transcranial Doppler sonography. Simultaneously the arterial blood pressure was recorded using a photoplethysmographic method. Two VM of 10 s length were performed per participant. Tracings of the variables were then transformed to equidistantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…First, all measurements were obtained far from the area undergoing remodeling caused by hemodynamic overload because of the malformation (20). Second, active venous tone regulation is consistent with the data on blood flow velocities in the straight sinus and MCA of healthy volunteers during different phases of the Valsalva maneuver (30). In the straight sinus, this parameter was found to be twice as high as that in the MCA during phase IV (overshoot phase), which is generally associated with transient blood pressure elevation caused by sympathetic nervous system activation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…First, all measurements were obtained far from the area undergoing remodeling caused by hemodynamic overload because of the malformation (20). Second, active venous tone regulation is consistent with the data on blood flow velocities in the straight sinus and MCA of healthy volunteers during different phases of the Valsalva maneuver (30). In the straight sinus, this parameter was found to be twice as high as that in the MCA during phase IV (overshoot phase), which is generally associated with transient blood pressure elevation caused by sympathetic nervous system activation.…”
Section: Discussionsupporting
confidence: 77%
“…Until recently, the indirect evidence for active cerebral venous regulation mostly stemmed from histochemical studies showing the presence of aminergic nerve endings in the venous wall (9,14,23), as well as from in vitro studies demonstrating venous wall responses to certain agonists (13,17). In addition, a recent study on healthy volunteers has also demonstrated an active response of intracranial cerebral veins during the overshoot phase of the Valsalva maneuver (30). To further elucidate which of the mechanisms is operative, either active control through venous wall reactivity or passive blood outflow with involvement of hydrodynamic factors alone, the present study has been undertaken.…”
mentioning
confidence: 99%
“…). The unequivocal identification of the other phases requires averaging of several Doppler recordings . Furthermore, reflux defined as a flow direction toward the cranium was registered.…”
Section: Methodsmentioning
confidence: 99%
“…Effect of a Valsava Maneuver on the intracranial venous circulation. A) Schematic change of venous flow velocities during and after a Valsalva maneuver based on data of Stolz et al . B) Example of flow velocity measurement in the basal vein.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, some humans studies reported indicate that the cerebral veins may possess an active rather than passive regulation of cerebral venous tone under some situations (Stolz et al. , ; Ivanov et al. ).…”
Section: Discussionmentioning
confidence: 99%